1993
DOI: 10.1161/01.str.24.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Modification of hypoxia-induced injury in cultured rat astrocytes by high levels of glucose.

Abstract: Background and Purpose: Preexisting hyperglycemia exacerbates central nervous system injury after transient global and focal cerebral ischemia. Increased anaerobic metabolism with resultant lactic acidosis has been shown to cause the hyperglycemic, neuronal injury. The contribution of astrocytes in producing lactic acidosis under hyperglycemic/ischemic conditions is unclear, whereas the protective role of astrocytes in ischemic-induced neuronal injury has been documented. The ability of astrocytes to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 66 publications
(8 reference statements)
3
33
1
1
Order By: Relevance
“…(1991a, b & 1992). It is unlikely that hyperosmolarity accounted for fructose-I ,6-bisphosphate's protective or injurious effects, since we found no evidence that fructose-l,6-bisphosphate induced hyperosmolarity in vivo (Sola et al 1996) nor did we find hyperosmolar-induced injury in primary cultures of astrocytes (Kelleher et al 1993).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…(1991a, b & 1992). It is unlikely that hyperosmolarity accounted for fructose-I ,6-bisphosphate's protective or injurious effects, since we found no evidence that fructose-l,6-bisphosphate induced hyperosmolarity in vivo (Sola et al 1996) nor did we find hyperosmolar-induced injury in primary cultures of astrocytes (Kelleher et al 1993).…”
Section: Discussioncontrasting
confidence: 63%
“…Perinatal hypoxia-ischaemia is associated with alterations in phosphate concentrations, ATP/phosphate ratios, and calcium concentrations of the brain (Vannucci 1993). Giving fructose-I ,6-bisphosphate during or immediately after hypoxia-ischaemia reduces ATP loss from the heart (Horster & Lewy 1970;Ichikawa et al 1979) and from cultured astrocytes Kelleher et al 1993Kelleher et al & 1994. The mechanism of this protection is unknown, but the present studies in rat pups and those in brain slices (Bickler & Kelleher 1992), myocardial tissue (Galzinga et al 1989), and spermatozoa (Fasolato et a/.…”
Section: Discussionmentioning
confidence: 72%
“…This might aid in maintaining the intracellular ATP levels in hypoxic astrocytic cultures at levels sufficient for survival (Yager et al, 1994). Furthermore, hyperglycemia promotes survival of astrocytes exposed to hypoxia/ischemia (Callahan et al, 1990;Kelleher et al, 1993). Some studies have shown that neurons may actually be more resistant than astrocytes to hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxia and hypoxic related injuries to the brain, astrocytes although moderately resilient to injury undergo changes that compromise their abilities to provide support and can even act as executioners of cellular demise. Astrocytes themselves in in vitro models can survive severe hypoxia for up to 96 hours and anoxia for 12-24 hours (Yu et al, 1989;Kelleher et al, 1993;Sochocka et al, 1994). In Middle Cerebral Artery Occlusion (MCAO) rat models, astrocytes experience morphological changes and swelling as early as 30 minutes after occlusion, followed by an increase in GFAP reactivity by six hours and astrocyte death at 24 hours (Garcia et al, 1993).…”
Section: Astrocytes: Targets For Neuroprotection In Cns Diseasesmentioning
confidence: 99%